THE EFFECT OF GROSS MOTOR AND FINE MOTOR STIMULATIONS ON THE DEVELOPMENT OF BABIES AGED 3-6 MONTHS - Nurul Aziza Ath Thaariq; Mariza Mustika Dewi; Niken Wahyu Hidayati; Erindra Budi Cahyanto (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Toddler is a crucial phase as the child’s brain is developing rapidly during this period. In this stage, it is important to assess the child’s stimulation to detect any abnormality as early as possible. The earlier the growth and development retardation are detected, the treatment or stimulation intervention can produce more effective results. Aims: The objective of this study is to determine the effect of the gross stimulation and the fine motor stimulation on the development of babies aged 3-6 months. Methods: This research used the quasi experimental method with one group pre- and post-test design. The research was conducted at Community Health Center of Ngoresan. The samples were 20 respondents (babies with dubious development), chosen by using the quota sampling technique. The data of the research were analyzed statistically by using Wilcoxon test. Results: There is a difference in the baby development mean value prior to and after following the gross stimulation and the fine motor stimulation, that is 7.85 and 9.5 respectively with the value of p = 0.000. Conclusion: Gross and fine motor stimulations affect the development of babies.